2017
DOI: 10.17159/2413-3221/2017/v45n2a443
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of policies promoting sustainable agriculture in South Africa

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The ever-increasing world population exacerbates cries for food security and an intensified effort in climate change as well as land-use changes which are brought by increased agricultural production. Khwidzhili and Worth (2017) pointed out that the world population puts more strain on agricultural lands, particularly the rain-fed arable lands.…”
Section: ‹ 71 ›mentioning
confidence: 99%
See 2 more Smart Citations
“…The ever-increasing world population exacerbates cries for food security and an intensified effort in climate change as well as land-use changes which are brought by increased agricultural production. Khwidzhili and Worth (2017) pointed out that the world population puts more strain on agricultural lands, particularly the rain-fed arable lands.…”
Section: ‹ 71 ›mentioning
confidence: 99%
“…Recent studies have shown that the overuse of nitrogenous fertiliser is a significant cause of economic loss in the agricultural sector. In the case of South Africa, with increased demand due to increasing population, there has been a challenge of balancing agriculture development and ensuring environmental sustainability (Khwidzhili & Worth, 2017). Available literature shows that efficient and eco-friendly cropping systems are increasingly studied to improve water-use efficiency and nutrient management (Musvoto et al, 2015).…”
Section: ‹ 71 ›mentioning
confidence: 99%
See 1 more Smart Citation
“…The main objective of this study was to evaluate South African public agricultural extension and its alignment to the five pillars of sustainable agriculture. The premise of the study was that there is no inclusive policy dealing specifically with sustainable agricultural practices in South Africa (Khwidzhili & Worth, 2017). Thus, it was necessary to study various policies to determine the criteria being used when discussing or promoting sustainable agriculture.…”
Section: Findings and Implications Of The Studymentioning
confidence: 99%
“…Kleinbooi (2010) suggested the need to review the procedures used in exploring studies researching small-scale agriculture to ensure it accurately records the role of small-scale agriculture and its potential in contributing to rural economic development. The contribution of small-agriculture in the South African rural economy is not well recognised or documented because there is a dearth of environmental policies supporting and protecting rural farmers from all possible risks they may face (Khwidzhili & Worth, 2017). This has resulted in negative outcomes on the role of small-scale agriculture in accessing the market and its contribution to the GDP to enhance the rural economy.…”
Section: Literature Reviewmentioning
confidence: 99%